Pelatihan Pembelajaran Nilai-Nilai Moral Anak Usia Dini Dengan Pendekatan Saintifik di IGRA (Ikatan Guru Raudhatul Athfal) Sidoarjo - Indaria Tri Hariyani; Noviardani Kartika Prameswari; Norma Diana Fitri (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2023)
Training on Learning Moral Values of Early Childhood with a Scientific Approach at IGRA (Raudhatul Athfal Teacher Association) Sidoarjo" aims to provide three provisions to partners, namely: 1. Understanding and insight into learning moral values of early childhood based on a scientific approach; 2. Providing adequate abilities and skills regarding learning moral values for early childhood with a scientific approach so that learning will be more successful; 3. the ability to practice directly learning the moral values of early childhood with a scientific approach. The partners included were 40 teachers registered with IGRA (Raudhatul Athfal Teachers' Association). The implementation method uses a comprehensive method, in the sense of involving partners from the beginning of implementation to the end of the service, namely by inviting partners to identify problems related to partners' difficulties in terms of learning moral values for early childhood. Besides that, it involves partners to be directly involved in activities by providing the widest possible opportunity for partners to ask questions, respond and share experiences. The activity steps include: 1. Orientation of the material by presenting the material by the resource person; 2. Provide concrete examples of a scientific approach in learning moral values for early childhood; 3. Provide hands-on practice of a scientific approach in learning moral values at an early age. The results of the activity show three things, namely: Increased understanding and comprehensive insight of partners about learning moral values for early childhood with a scientific approach, as evidenced from the results of interviews 95% of partners said their understanding and insight had increased; 2. The level of ability and skills of partners regarding learning moral values for early childhood with a scientific approach has also increased, as evidenced by the results of interviews, 85% of partners have increased their abilities and skills; . The ability of partners when directly practicing learning moral values of early childhood with a scientific approach is also quite proven from the results of observations 85% of partners are able to carry out the practice.